Development and evaluation of mucosal tuberculosis vaccine utilizing in-trans surface display system of Lactobacillus plantarum Pa21 in mice - Mustafa, Anhar Danial (2017)
The severity of tuberculosis is significant since it has been estimated to have latently affected almost a third of the world’s population with Mycobacterium tuberculosis, the causative agent for tuberculosis. Fortunately, the disease is being prevented and controlled by the Bacille Calmette Guérin (BCG) vaccine, the only viable vaccine approved for human usage since 1921. Nevertheless, the protective efficacy of the BCG vaccine has been highly variable and substandard (0-80%) in adults especially in endemic regions due to pre-existing immune responses to the vaccine. Therefore, there is a strong need for new and effective tuberculosis vaccine to be developed either as a replacement or as a booster in order to overcome the limitations from BCG vaccine. In this project, candidate mucosal tuberculosis vaccines utilizing protein surface display system of Lactobacillus plantarum carrying and displaying five combinations of M. tuberculosis subunit epitope antigens (Ag85B, CFP-10, ESAT-6, Rv0475 and Rv2031c) fused with LysM anchor motif were constructed, cloned and expressed in Esherichia coli Rossetta expression host. By using the in trans approach, the recombinant protein of interest were expressed in E. coli and extracted before being applied for extracellular attachment onto the cell wall of L. plantarum. Subsequently the binding capability of the recombinant protein of interest to the cell wall of L. plantarum was examined via the immunofluorescence microscopy and whole cell ELISA approaches where successful attachment and consistent stability of cell wall binding up to four days period was determined. Although the five recombinant protein of interest were expressed successfully, their expressions were found to be deposited in the inclusion bodies (IBs) of the E. coli. To overcome this, the solubilization on the IBs was optimized via the 5% (w/v) N-lauryl sarcosine treatment but among the five recombinant protein of interest, only ACERL was managed to be recovered optimally (38.2% extractability) for further usage in animal study. Therefore the immunization of the female Balb/c mice with the developed vaccine of L. plantarum surface displaying ACERL (Lp ACERL) via the oral and intranasal route of administration were studied for its immunogenicity effects. Significant increase in total IgG antibody response and high CD4+/CD8+ ratio from the Lp ACERL immunized oral group as compared to nasal group indicates high reactivity of the developed vaccine in being recognized by the host immune system. Moreover, unlike the nasal group, Lp ACERL of orally immunized mice was able to invoke strong mucosal and systemic immune responses as indicated by the specific IgA antibody response from the immunized mice’s gastrointestinal tract (GIT), feacal and serum samples. More importantly, Lp ACERL of orally immunized mice showed immune response that favors the Th1 type response as indicated by the immune response outcome from the cytokine profiling of spleen, lung and GIT, and the re-stimulation of the splenocytes from the immunized mice. In contrast, the Lp ACERL intranasally immunized mice does not show significant correlation for inducing neither Th1 nor Th2 immune response. However, this may be due to severe inflammation on the lung of the nasally immunized mice that might compromised its overall immune response outcome. The effect of adding adjuvant consisting of Lactococcus lactis secreting mouse IL-12 (LcIL-12) co-administered with Lp ACERL was also determined as it shown to induced a more favorable condition for the candidate vaccine to further generate significant and bias of Th1 protective immune responses as compared to the immune response from the immunization with Lp ACERL alone. The enhancement of the Th1 type responses were observed from the serum IgG sub-types and the cytokine profiling of spleen, lung and GIT immune response outcome. Thus, this study shows that the developed candidate vaccine of Lp ACERL with or without LcIL-12 adjuvant was able to stimulate favorable Th1 type response which is the key indicator for inducing effective protective memory response required for the prevention of tuberculosis. In conclusion,, this study represents a proof of concept in the development of L. plantarum as a carrier for a non-genetically modified organism (GMO) tuberculosis vaccine, which may be the strategy in the future for tuberculosis vaccine development.